Minimally Destructive Bamboo Property Estimation of Phyllostachys makinoi Using Drilling Resistance Method - Cheng-Jung Lin; Po-Heng Lin (BioResources)
Drilling resistance amplitude was used to estimate properties such as density, modulus of elasticity (MOE), and modulus of rupture (MOR) in Phyllostachys makinoi bamboo. The purpose of this study was to replace subjective visual estimation with a scientific method, using drilling resistance to estimate bamboo maturity, thereby providing a basis for selecting high-quality bamboo materials. The results indicated significant linear correlations between both average and maximum drilling amplitudes and bamboo density, MOE, and MOR. The coefficients of determination (R²) for average and maximum drilling amplitude with bamboo density ranged between 0.55 and 0.56, and a significant linear correlation was also observed between average and maximum drilling amplitudes (R² = 0.75). Additionally, the profile curve of drilling resistance amplitude varied significantly across the thickness of the bamboo culm. From the culm surface inward (bamboo skin, flesh layer, and cavity layer), the amplitude rose rapidly, reaching a peak at approximately 28% of culm thickness, then gradually decreased, with a secondary reduction observed around 67% of the thickness, eventually reaching the hollow core. Based on these findings, maximum drilling amplitude could serve as an indicator of bamboo density and may be applied as a minimally destructive technique for evaluating bamboo quality.